Assessing the Barriers of Strategic Plan Implementation from Hospital Managers\' Perspective in Kerman City - ahmad amerion; mostafa shahabi nejad (Tehran University of Medical Sciences, 2016)
Background: Strategic plan in hospitals will not be run spontaneously and managers encountered with some barriers in order to have a successful strategic planning implementation. This study aimed at recognizing the barriers of strategic plan implementation from hospital managerschr('39') perspective. Materials and Methods: This cross-sectional study was performed in all Kerman hospitals in 2014. Fifty three individuals including chairmen, internal administrators, quality improvement managers, matrons and strategic plan executers participated by census sampling method. Data was collected using a questionnaire including demographic information and human, processes, structures and institutions factors affecting the strategies implementation. Data analysis was performed by SPSS software version21. Results:  Study results revealed that the barriers to strategic plan implementation were structural factors (27.71±6.68), process agents (19.54±10.06), human factors (19.09±5.37) and institutional factors (15.73±4.52) respectively. There was no significant association between management background and barriers of strategic plan implementation in hospitals (P < 0.05). Conclusions: In order to achieve desired results, chairmen and hospitals managers should be entirely conscious about barriers /failure factors of strategic decisions concerning foresight and appropriate managing or approaches change during strategic management process implementation.